Identification of neutrophil activation markers as novel surrogate markers of CF lung disease - Rath, Timo; Zwaschka, Lisa; Hage, Lisa; Kügler, Marion; Menendez, Katrin; Naehrlich, Lutz; Schulz, Richard; Roderfeld, Martin; Roeb, Elke; Justus Liebig University Giessen (My University, 2014)
Background and aims: Cystic Fibrosis (CF) lung disease is characterized by progressively declining lung function and represents a major factor contributing to the high morbidity and mortality associated with CF. However, apart from spirometry, respiratory disease surrogate markers reliably indicating CF lung disease and the occurrence of pulmonary exacerbations (PEx) are still lacking. Within this study, we aimed to identify new experimental biomarkers for the detection of CF lung disease. Methods: 54 adult and 26 pediatric CF patients were included in the study and serum concentrations of MMP-1, -2, -8, -9, -13, TIMP-1, TIMP-2, YKL-40, hyaluronic acid, procollagen III peptide were quantified by ELISA. CF lung disease was diagnosed by lung function test, PEx was defined based on a clinical scoring established by Rosenfeld in 2001. Results: Adults and children with moderate to severe CF lung disease exhibited significantly increased serum expression of MMP-8, MMP-9, YKL-40 and TIMP-1. Further, MMP-8, MMP-9 and YKL-40 were significantly increased in adult CF patients suffering from PEx compared to those without clinical signs of respiratory exacerbation. MMP-8, MMP-9, YKL-40, and TIMP-1 serum levels were unaffected by the presence or absence of CF liver disease or pancreatic insufficiency. Conclusions: MMP-8, MMP-9, and YKL-40 might serve as novel non-invasive biomarkers of CF lung disease and PEx.
Keywords: ddc:610